How is mhealth and web-based telemedicine implemented in patient with hypertension? : a narrative scoping review - Gautama, Made Satya Nugraha (Sahabat Publikasi Kuu, 2023)
In this digital era, telemedicine has become one of the cutting-edge approaches that is feasible for hypertension management. Despite the proliferation of trial research, reviews of how telemedicine is practiced are limited. The aim of this study is to review how telehealth is applied in patients with hypertension. A scoping review according to the Joanna Briggs Institute Reviewer Manual's instructions was used with a narrative approach to the type of RCT intervention articles. The search was conducted through electronic databases Scopus, PubMed, and Medline-OVID with the keywords